Avaliação da participação espinal dos sistemas endocanabinoide e opioide na antinocicepção induzida pela terapia por ondas de choque em camundongos com dor pós-operatória. - Malta, Iago Henrique Silva (2023)
Post-operative pain (POP) occurs after surgical procedures and, despite being an expected event, it affects the individual's quality of life and functionality. If not managed properly, this pain can become chronic, causing a persistent problem. The treatment of choice for this type of pain is pharmacological therapy and, despite its effectiveness, this modality has adverse adverse effects. Thus, non-pharmacological therapies, such as shock wave therapy (SWT), attenuate musculoskeletal pain with fewer adverse effects. However, little is known about the antinociceptive effect of SWT, specially in the central nervous system. Therefore, the objective was to investigate the spinal participation of the endocannabinoid system (ECS) and the opioid system (OPS) in the antinociceptive effect of SWT in mice with POP. For this, male C57BL/6 mice were submitted to skin and muscle incision and retraction surgery (SMIR) in the right thigh for POP induction. The nociceptive threshold of these animals was evaluated using von Frey monofilaments. SMIR surgery induced POP from the 1st to the 28th postoperative day. The animals then received two applications, on the 14th and 16th postoperative days, of 100, 200, or 400 SWT pulses, with an energy flux density of 0.11 mJ/mm 2 , 10 Hz, on an application area of 5 mm of the medial region of the right thigh, or sham treatment. On the 16th day, after the second application of SWT, the nociceptive threshold was evaluated again. 100 and 200 pulses of SWT reduced POP for 60 minutes. The participation of CB 1 and CB 2 receptors was evaluated by pre-administration on the 16th day (right before the second SWT application) of the selective antagonists for CB 1 , AM251 (0.1, 1, and 10 µg), and CB 2 , AM630 (3, 6, and 12 µg), and there was a dose-dependent reduction in SWT antinociception. On the other hand, pre-administration of the anandamide (AEA) reuptake inhibitor VDM11 (1, 2, and 4 µg) and the monoacylglycerol lipase (MAGL) enzyme inhibitor JZL184 (0.5, 1 and 2 µg) potentiated and prolonged the antinociception of SWT. Likewise, the pre- administration of Naloxone (1, 2, and 4 μg), a non-selective opioid receptor antagonist, Cloccinamox (1, 2, and 4 μg), a selective μ opioid receptor antagonist, and Nor-binaltorphimine (1.25, 2.5, and 5 μg), a selective antagonist of opioid κ receptors, showed that the antagonization of opioid receptors, non-selectively and selectively, decreased in a dose-dependent manner the antinociception induced by SWT. Assessment in the 16th day of spinal AEA and 2-arachidonoylglycerol (2-AG) levels by liquid chromatography/mass spectrometry revealed an increase in 2-AG levels only in treated animals. Western Blot analysis showed a decrease in the spinal expression of MAGL, but there was no change between groups in the expression of CB 1 , CB 2 , and the enzyme fatty acid amide hydrolase (FAAH). In addition, spinal evaluation of μ, κ, and δ opioid receptor expression showed no statistical difference between groups. Finally, spinal evaluation of IL-1β, TNF-ɑ, and IL-10 cytokine levels by ELISA technique showed a reduction in IL-1β levels in SWT-treated animals with POP when compared to untreated animals, but no difference between groups was identified for the other cytokines. Based on the findings of the present study, it is possible to suggest that SWT attenuates POP and that both ECS and OPS may participate in the antinociceptive effect of this therapy.